Revolutionizing Finance: Decentralized Finance as a Disruptive Challenge to Traditional Finance - MIRDALA, Rajmund (Theoretical and Practical Research in Economic Fields; Vol 15 No 3 (2024): TPREF, Volume XV, Issue 3(31), Fall 2024, 2024)
This paper examines the emergence and impact of Decentralized Finance (DeFi), between 2019 and 2024, as a disruptive agent opposing traditional finance (TradFi). By using blockchain technology to offer decentralized, open, and readily available financial services, the DeFi industry has seen explosive expansion Emphasizing DeFi's competitive advantage over TradFi, this study aims to investigate notable trends, developments, and market drivers in the toolkit. The main conclusions are the fast and significant rise in Total Value Locked (TVL), the clear increase in user adoption, the expansion in the number of transactions and trading volume on decentralized exchanges (DEXs), and the development of creative financial products. DeFi constantly changes the financial scene despite regulatory oversight and market volatility, so posing major problems and opportunities for established financial institutions.